2020
DOI: 10.3390/agronomy10111696
|View full text |Cite
|
Sign up to set email alerts
|

Annual Wildflower Strips as a Tool for Enhancing Functional Biodiversity in Rye Fields in an Organic Cultivation System

Abstract: Ecological intensification of agriculture (e.g., with the use of wildflower strips) is being currently discussed as a mean for gaining high yields, preserving high biodiversity of farmland. The aim of this study was to assess the efficiency of annual wildflower strips (WFSs) established in rye field (RF) in (1) increasing species richness and abundance in terms of beneficial arthropod groups (carabids, ground spiders, plant spiders, butterflies, insect pollinators and plant-dwelling insect predators), (2) decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Bumblebees were virtually absent from the typical greenways sown with grasses. In research by Kujawa et al [22], 14 butterfly species of five families were observed in flower strips, and the most abundant species was Vanessa cardui L. (54%). As shown by our one-year observations (unpublished data from western Poland, 2022), the most frequently occurring butterfly in a flower strip was Aglais io L., which mostly favoured the inflorescence of Trifolium pratense (L.).…”
Section: Pollinatorsmentioning
confidence: 96%
See 2 more Smart Citations
“…Bumblebees were virtually absent from the typical greenways sown with grasses. In research by Kujawa et al [22], 14 butterfly species of five families were observed in flower strips, and the most abundant species was Vanessa cardui L. (54%). As shown by our one-year observations (unpublished data from western Poland, 2022), the most frequently occurring butterfly in a flower strip was Aglais io L., which mostly favoured the inflorescence of Trifolium pratense (L.).…”
Section: Pollinatorsmentioning
confidence: 96%
“…Unfortunately, due to the disappearance of refuges in fields, carabids are facing extinction [2,26]. Kujawa et al [22] reported that as many as 46 carabid species were observed in flower strips. The most abundant species was Harpalus rufipes (hemizoophage, feeding on both plants and animals), which constituted 45.8% of the particular beetle numbers, and the most abundant of the 47 ground spider species was Pardosa agrestis (24% of all individuals).…”
Section: Natural Enemies Of Insect Pestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such spillover and the effect of AEI in general on the adjacent crops have been mainly investigated through the measurement of the abundance and richness of beneficial arthropods. Some studies showed such spillover effect (Gayer et al, 2019;Woodcock et al, 2016), but in others, this could not be clearly observed (Kujawa et al, 2020;Triquet et al, 2022). Indeed, little is known about this process, and particularly about the impact of AEI on the composition and the ecological trait distribution of arthropod communities in adjacent fields at different distances from the AEI (Boetzl et al, 2018;Gallé et al, 2020;Gayer et al, 2019;Pecheur et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, placed at the edge of cropped fields, they have a particular interest for multiple ecosystem services, for example, water regulation and purification, and prevention of soil erosion. Many studies have shown the attractiveness of vegetation strips for a large range of beneficial arthropods (Campbell et al, 2019; Holland et al, 2016; Kujawa et al, 2020; Triquet et al, 2022) including pollinators when they contain flowers (Amy et al, 2018; Haaland et al, 2011). They can offer food resources, shelter (Griffiths et al, 2008; Landis et al, 2005), and overwintering habitat for ground‐dwelling arthropods (Landis et al, 2000; Pywell et al, 2005), and thus are expected to deliver ecosystem services to adjacent cropping (Bianchi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%